New novel physical constants metric and fine structure constant models demonstrate the intrinsic nature of vacuum space as a quantum medium - Markoulakis, Emmanouil; Wolf, Christian (International Journal of Physical Research, 2023)
We hereby display two independent research-wise blind folded calculations of the fine structure constant using different angles in attacking the problem by two different novel models that however produced the same result which leads to the inescapable conclusion that 'empty' vacuum space must be intrinsically a quantized medium in nature.